Alterações fisiológicas, percepção subjetiva de esforço e percepção de conforto durante formatura militar: um estudo experimental - Gonçalves, Michel Moraes; Miranda, Humberto Lameira; Neves, Eduardo Borba; Machado, Fabio Alves; Valente, Antonio Marcio dos Santos; Inoue, Allan; Marson, Runer Augusto (Revista de Educação Física / Journal of Physical Education, 2019)
Introdução: Em formaturas militares a posição ortostática (em pé), com a máxima imobilidade, é um fator exigido e, muitas vezes, suportando cargas externas. Para se adaptar a este esforço alterações fisiológicas são necessárias, porém podem ser prejudiciais. Entretanto, para tornar a atividade menos desgastante e sem comprometer a marcialidade do cerimonial militar, ajustes posturais podem ser sugeridos. Objetivo: Observar as alterações de frequência cardíaca máxima (FCMáx), percentual de saturação de oxigênio (%SatO2), perímetro da panturrilha (PP), percepção subjetiva de esforço (PSE) e de percepção de conforto, comparando períodos de permanência na posição ortostática com e sem breve período de livre postura e com e sem sobrecarga de peso externo. Métodos: Estudo experimental de seção transversal, modelo cross-over, do qual participaram 24 militares do sexo masculino. Foram executados dois protocolos (P1 e P2) simulando uma formatura de 33 minutos, em pé, com a máxima imobilidade, com carga externa (mochila operacional). Em ambos, foram executados comandos de “sentido e descansar” a cada 5 minutos, porém, somente em P2 os sujeitos puderam retirar a carga externa e permanecer em livre postura por 5 minutos. Foram realizadas medidas de FCmáx (bpm), %SatO2 (%), PP (cm), PSE e percepção de conforto. Foram realizados testes estatísticos ANOVA de medidas repetidas, ANOVA fatorial, U de Mann Whitney, Wilcoxon e correlação de Spearman. Resultados: Houve aumento no PP, com diferença estatística significativa entre o minuto 13 (38,75 ± 5,91cm) e o minuto 33 (37,67 ± 4,62cm) em P1 (protocolo sem intervalo para “período de livre postura”), mas o mesmo não ocorreu em P2. Observou-se um aumento mais acentuado na FCmáx ao longo do tempo em P1, foram encontradas diferenças significativas apenas em P1, em todos os momentos após M16 (M21 = 80,58 ± 13,49 bpm; M26 = 79,08 ± 10,61 bpm; M31 = 83,67 ± 11,77 bpm e M33 = 80,00 ± 12,80 bpm) em relação ao primeiro minuto (M1=71,71 ± 15,29 bpm). Não houve diferenças no %SatO2. Não foi encontrada diferença significativa na PSE, nem na percepção de conforto entre os protocolos. Conclusão: Um período de 5 minutos, com livre postura e sem a mochila operacional, em formatura militar, parece ter um efeito protetor em relação a alguns efeitos fisiológicos causados por este tipo de esforço, embora não pareça influenciar na percepção de esforço e percepção de conforto entre militares. Physiological Changes, Perceived Exertion and Perceived Comfort During Military Parade: An Experimental Study Introduction: Introduction: In military graduations the individual must be in an orthostatic (standing) position, with maximum immobility and, often, bearing external loads. To adapt to this effort, physiological changes occur which can be harmful. However, strategies can be adopted to alleviate these changes, making the activity less exhausting, without compromising the martial nature of the military ceremonial. Objective: Observe changes in maximal heart rate (HRmax), oxygen saturation percentage (% SatO2), calf girth (CG), subjective exertion perception (SEP) and comfort perception, comparing periods of standing in the standing position with and without a short period of free posture and with and without external weight overload.Introduction: Introduction: In military graduations the individual must be in an orthostatic (standing) position, with maximum immobility and, often, bearing external loads. To adapt to this effort, physiological changes occur which can be harmful. However, strategies can be adopted to alleviate these changes, making the activity less exhausting, without compromising the martial nature of the military ceremonial. Methods: Experimental cross-sectional study, cross-over model, involving 24 male military personnel. Two protocols were executed (P1 and P2) simulating a 33-minute standing graduation, with maximum immobility, with external load (operational backpack). In both protocols, "sense and rest" commands were executed every 5 minutes, but only in P2 the subjects could remove the external load and remain in a relaxed position for 5 minutes, in the sixteenth minute of the simulation. Measurements of maximum heart rate - HRmax (bpm), percentage of oxygen saturation -% SatO2 (%), calf perimeter - PP (cm), subjective perception of effort (PSE) and comfort were performed. Statistical tests were performed using repeated measures ANOVA, factorial ANOVA, U de Mann Whitney, Wilcoxon and Spearman correlation Results: An increase in calf circumference was found, with a significant statistical difference between minute 13 (38,75 ± 5,91cm) and minute 33 (37,67 ± 4,62cm) in P1 (protocol no rest for "period of free posture ), but the same did not occur in P2. A more pronounced increase in heart rate over time was observed in P1, significant differences were found only in P1, at all times after the interval (M21 = 80,58 ± 13,49 bpm; M26 = 79,08 ± 10,61 bpm; M31 = 83,67 ± 11,77 bpm e M33 = 80,00 ± 12,80 bpm) in relation to the first minute (M1=71,71 ± 15,29 bpm). There were no differences in % SatO2. No significant difference was found in PSE, but it was found in the perception of comfort. Conclusion: A period of free posture during for 5 minutes without the backpack operational, in military parade, seems to have an effect protection against some physiological effects caused by this type of effort, although it not seems to influence the perception of effort and perception of comfort in military personnel.